Inclusión de lodo de palma en la dieta de codornices hembras (Coturnix coturnix) en la etapa de crecimiento y arranque de la postura - Troya Murillo, Xiomara Lilibeth (2023)
Any producer dedicated to raising quails is faced with optimizing their profits and improving the profitability that this species and its by-products can produce. The following investigation which consists of obtaining knowledge from a study or practical experience, establishing new processes, this consists of adding a by-product of nature obtained from the palm, including its sludge to continue the production of quail in two stages. Factor A (food alternative) More balanced palm mud and the methods used in the investigation were the following: Quantitative, Meta-analysis, Experimental, Hypothetical deductive. According to ESPAC, which are the main sources of official information on the agricultural sector, the latest statistics on the quail population in 2021 was 47,574 in Ecuador. The DCA completely randomized design will be used, which provides the possibility that the treatments are assigned to the random experimental units without any restriction. The results of the experimental investigation will be described where certain specific response variables to be studied and the conditions in which they were presented. the initials in which the experimental subjects arrived and in the same way their completion so that with a probability of 5% in the TUKEY and DUNCAN methods, treatment 3 is the one that has gained the most weight weekly, being highly significant in the last week with an average of 0.0476 reached with its feeding through the respective treatment and when breaking posture of the two weeks with the following averages 0.0200 in the first and 0.0447 in the second.